(untitled) (Journal of Uzbekistan’s Development and Research, 2025)
This article examines the role of culinary festivals and events in promoting gastronomic tourism in Uzbekistan, with a focus on leveraging the country’s rich culinary heritage to attract tourists. It explores Uzbekistan’s diverse and historically significant cuisine, the current state of gastronomic tourism, and emerging opportunities for development.